Optimal Endpoint of Therapy in IBD: An Update on Factors Determining a Successful Drug Withdrawal - Anita Annaházi; Tamás Molnár (Gastroenterology Research and Practice)
Ulcerative colitis (UC) and Crohn’s disease (CD) are chronic inflammatory disorders, which require long term treatment to achieve remission and to prevent relapses and cancer. While current therapies are effective in most cases, they can have rare but serious side effects and are often associated with high costs. On the other hand, early discontinuation of an effective treatment may lead to a quick relapse and to complications at the restart of therapy. Therefore it is essential to determine the optimal duration of maintenance therapy, but clear guidelines are missing. The most important questions when deciding whether to continue or withdraw therapy in quiescent UC and CD patients are the efficacy of the continuous treatment to maintain remission in the long term, the frequency and severity of side effects, and the chance of relapse after discontinuation of therapy. This review summarizes the current knowledge on these topics with respect to 5-aminosalicylates, thiopurines, methotrexate, and biological therapies and collects information regarding when and in which specific patient groups, in the absence of risk factors, can withdrawal of therapy be considered without a high risk of relapse. Additionally, the particular aspect of colorectal cancer prevention by current therapies will also be discussed.